Flavones and lignanes from Glochidion obliquum Decne - Thu, Vu Kim; Thang, Nguyen Van; Tuan Anh, Hoang Le; Nhiem, Nguyen Xuan; Thuy Hang, Dan Thi; Minh, Chau Van; Kiem, Phan Van (Vietnam Journal of Chemistry, 2016)
Using combined chromatographic methods, two flavones, vitexin (1) and 6''-O-acetylorientin (2), and two lignanes, (+)-pinoresinol (3) and (+)-syringaresinol (4) were isolated from the methanol extract of the leaves of Glochidion obliquum Decne. Their structures were elucidated by 1D- and 2D-NMR spectra and in comparison with those reported in the literature. Keywords. Glochidion obliquum, flavone, lignane, vitexin, 6''-O-acetylorientin, pinoresinol, syringaresinol.